THE ROLE OF MODERN SCULPTURE IN UZBEKISTAN: A FUSION OF TRADITION AND CONTEMPORARY EXPRESSION - Alimardon Khaydaraliyevich Abdullaev (Galaxy International Interdisciplinary Research Journal, 2023)
This scientific article explores the role of modern sculpture in Uzbekistan, focusing on its contribution to the artistic landscape and the synthesis of traditional Uzbek culture with contemporary artistic expression. Uzbekistan, with its rich cultural heritage and ancient history, has witnessed the evolution of sculpture from traditional forms to the advent of modern and innovative artistic approaches. This article analyzes the factors influencing the development of modern sculpture, highlights significant sculptors and artworks, and elucidates how modern sculpture bridges the gap between heritage and innovation.